Jurusan Akuntansi Fakultas Ekonomi Universitas Udayana - ADNYANA USADHA, I PUTU; WIRAWAN YASA, GERIANTA (Jurnal Ilmiah Akuntansi dan Bisnis, 2009)
The purpose of this research is to gain empirical evidence whetheracquiring companies conduct earnings management before the execution ofmerger and acquisition. It also aims to investigate performance changes ofacquiring companies before and after merger and acquisition.Earnings management conducted by the companies is proxied bydiscretionary accrual (DA). Analysis is done using independent sample ttestand paired sample test. The result shows that there is an indication ofearnings management done by taking over companies before merger andacquisition by utilizing income increasing accruals. Furthermore, thefinancial performance of the companies is lower after merger andacquisition took place.
Keywords: merger, acquisition, earnings management, performance